Optimizing Digital Accounting to Improve MSME Performance through the Quality of Accounting Information - Hendrawati, Erna; Kholidiah, Kholidiah; Pramudianti, Mira (International Journal of Social and Management Studies, 2024)
This study examines the impact of digital accounting usage on the performance of SMEs participating in the e-peken platform in Surabaya, with accounting information quality as a mediating variable. Using a quantitative method with SEM-PLS analysis, this research involved 350 SMEs as respondents. The results show that digital accounting usage positively influences accounting information quality, and accounting information quality positively affects SME performance. However, digital accounting usage does not directly influence SME performance. Accounting information quality is proven to mediate the relationship between digital accounting usage and SME performance. These findings highlight the importance of focusing on improving accounting information quality in digital technology adoption to enhance SME performance. The implications of this research include recommendations for developing comprehensive training programs and policies that support digital accounting adoption and improve financial literacy among SMEs.